Ministério público e políticas de saúde - Luciano Moreira de Oliveira (2013)
The 1988 Constitution ensured health as a fundamental right guided by the principles of universality, integrality, equity and the communitys participation while delegating to the state, as consideration, the duty to promote public policies for health promotion, protection and recovery. Also innovatively, the 1988 Constitution consolidated a new institutional profile to the Prosecuting Attorneys Office, put in charge of defending the rule of law, the democracy and the inalienable social and individual rights. These rights vested in the Prosecuting Attorneys Office, as well as the institutional functions described in the constitutional text, enable us to identify a close relationship between that governmental institution and the right to health, it being incumbent on the institute to take the steps needed to safeguard that right and ensure that both government and private parties alike respect it. Thus, the work of the Prosecuting Attorneys Office has over the years, influenced the sanitary environment. Acting both in and out of court, the institution has juridicized social relations in a realm which has traditionally so far relied on the work of managers, service providers, health professionals, service users and academics. In practice however, it is possible to perceive the Offices distinct working methods insofar as it emphasizes the use of extrajudicial or judicial instruments, which comprise, in general terms, the resolving and the litigating models, respectively. This paper examines the effects of these different strategies to ensure the right to health, in addition to identifying the modus operandi of the Minas Gerais State Prosecuting Attorneys Office. Aims: Verify which of the operating models is the most adequate so that the Office can effectively contribute to ensure the right to health and identify its operating model as it safeguards the right to health. Methodology: This exploratory research purports to develop an interdisciplinary study, involving content from the health sciences, political sciences and law. At the outset, a review of the literature was done by researching the SCIELO, BIREME and CAPES databases and consulting reference works. To identify the Offices working methods, we have researched the institutions normative acts (regulations) addressing its work in the defense of health published in the states official gazette until December 31, 2012. All of these acts were reviewed in accordance with content analysis technique. Additionally, we have examined the data in the Single Register System (Sistema de RegistroÚnico, in Portuguese) on the proceedings recorded by the institution between January 1st, 2008 and December 31st, 2012. Results: We have verified that the work of the State Prosecuting Attorneys Office under the resolving model has proved to be the most adequate model to deal with the complexity of the right to health vis-à-vis the countrys health policies. Furthermore, the normative acts researched (n=30) evince the Offices emphasis on the resolving method, as corroborated by the study of the data that have shown that, despite a large record of proceedings in the studied period (n=13,224), judicialization was the exception, rather than the norm (n=1,567). Conclusion: The resolving model endows the institution with greater possibilities to tackle the complexities of the health policies and contribute more effectively to safeguard that right. Acting in this intersectorial manner, the Office contributes to build dialogued and empowering solutions to the right to health. The State Prosecuting Attorneys Office has organized itself in such a way as to prioritize the resolving method, which has reflected on the practice of its members.